2011
DOI: 10.1103/physrevd.83.044005
|View full text |Cite
|
Sign up to set email alerts
|

Kaluza-Klein models: Can we construct a viable example?

Abstract: In Kaluza-Klein models with toroidal compactification of the extra dimensions, we investigate soliton solutions of Einstein equation. The nonrelativistic gravitational potential of these solitons exactly coincides with the Newtonian one. We obtain the formulas for perihelion shift, deflection of light, time delay of radar echoes and post-Newtonian (PPN) parameters. Using the constraint on PPN parameter , we find that the solitonic parameter k should be very big: jkj ! 2:3 Â 10 4 . We define a soliton solution … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
68
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 27 publications
(74 citation statements)
references
References 29 publications
6
68
0
Order By: Relevance
“…We have shown in our previous paper [10] that the most natural point-like massive source with the dust-like equations of state in all dimensions contradicts the experimental data. The similar situation takes place in multidimensional linear models [11,12]. In such linear models, latent solitons, in particular, black strings and black branes, satisfy the gravitational experiments at the same level of accuracy as General Relativity.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…We have shown in our previous paper [10] that the most natural point-like massive source with the dust-like equations of state in all dimensions contradicts the experimental data. The similar situation takes place in multidimensional linear models [11,12]. In such linear models, latent solitons, in particular, black strings and black branes, satisfy the gravitational experiments at the same level of accuracy as General Relativity.…”
Section: Discussionmentioning
confidence: 89%
“…However, we have shown that such matter source contradicts the observations in the case of extra dimensions. The similar situation takes place in multidimensional linear models [11,12], where a point-like mass with dust-like equations of state in all spatial dimensions also contradicts the experimental data. However, latent solitons, in particular, black strings and black branes, satisfy the gravitational experiments at the same level of accuracy as General Relativity.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…In our previous papers [19,25,26] devoted to KK models with toroidal compactification of the extra dimensions, we have shown that gravitating masses should have tension in the internal space to be in agreement with gravitational experiments in the Solar system. For example, black strings/branes with the parameter ω = −1/2 in the equation of state in the internal space satisfy this condition.…”
Section: Introductionmentioning
confidence: 86%
“…Therefore, such measurements can be a very good test for gravitational theories. From our previous papers [19,25,26] we know that gravitating bodies should have pressure/tension in the extra dimensions to satisfy the observable data for the deflection of light and the experimental restrictions for the PPN parameter γ . In this regard, the question arises of the possibility of building a many-body Lagrange function in the presence of pressure/tension in the extra dimensions.…”
Section: Introductionmentioning
confidence: 99%